Factors Influencing Switching Intention of Medical Waste Bin with Push Pull Mooring Approach - Gaffar, Aditya; Lusiani, Mirna; Iskandar, Yelita Anggiane (Institut Ilmu Sosial dan Manajemen Stiami, 2022)
PT BINMED Ecomedika Industri (BINMED) is one of the companies engaged in the manufacture of medical devices in the form of special waste bins for sharps medical waste. Since starting to be marketed in 2019 until now, BINMED products have not reached the sales target. This is because conventional and/or non-standard safety boxes such as medical plastic bags, used bottles of mineral water in packaging, and jerry cans are still being used. In addition, BINMED products have just begun to be marketed in the Jabodetabek area using free trials and discounts. However, these two methods have not been able to attract the attention of potential buyers. Therefore, it is necessary to analyze the factors that influence prospective buyers to switch to using the BINMED safety box. The data collected were 72 samples using the purposive sampling technique to find the right respondents, namely prospective buyers working in the health sector. The variables used in this study include push effects (pricing, satisfaction, and trust), pull effects (attractive alternatives), and mooring effects (switching costs and subjective norms). Based on the results of data processing and analysis of research results, it was found that alternative interest had a significant effect on the intention to switch to the use of the safety box while the variables of pricing, satisfaction, trust, switching costs, subjective norms and the moderating effect of the mooring effects between push and pull effects and switching intentions did not affect switching intentions. The managerial implication that can be applied by the company is to promote on social media and cooperate with medical waste transport service providers who have collaborated with health facilities.